Investigation of the Characteristic and Sound Absorption Properties of a New Cellulose-based Fiber from Alcea rose L. Plant. Issue 15 (23rd November 2022) - Eyupoglu, Seyda; Merdan, Nigar
ABSTRACT: In this study, cellulose-based fibers were successfully obtained from Alcea rose L . plant stem of approximately 320 µm diameter, and then elemental analysis, surface morphology, functional groups analysis, crystallinity index, thermal stability, and mechanical behaviors were investigated. Furthermore, a surface was constituted with Alcea rose L . (ARL) fibers by the knitting technique, and sound absorption coefficient was measured. Elemental analysis results show that ARL fibers have 50.06% carbon and 49.84% oxygen. Morphology analysis indicates that the fibers have a rough surface and can support high interfacial strength when using as reinforcement in composites. Fourier transform infrared (FTIR) spectra and thermogravimetric analysis (TGA) confirm the presence of cellulose compound in fiber structure, also ARL fibers can be stable up to 361.39°C. The X-ray diffraction (XRD) analysis outcomes that ARL fibers have 80% crystallinity index with an average crystallinity size of 3.89 nm. Under the tensile load, ARL fibers tensile strength is 80.96 MPa and Young's modulus is 3.28 GPa with an elongation rate of 2.47%. The sound absorption of ARL surface is suitable ranges and it can be concluded that the fibers can be used as sound absorbers.